A new design approach of steel fibre reinforced ultra-high performance concrete composites: Experiments and modeling. (July 2020) - Fan, D.Q; Yu, R; Shui, Z.H; Wu, C.F; Song, Q.L; Liu, Z.J; Sun, Y; Gao, X; He, Y.J
Abstract: This paper addresses a new design of steel fibre reinforced ultra-high performance concrete (UHPC) composites by implanting the fibres into modified Andreasen and Andersen (MAA) particle packing model. A novel method for determining the equivalent spherical diameter of steel fibres is proposed, which preserves the effect on the wet particle packing of an UHPC system, when there are equal volume fractions of steel fibers or these extra spherical particles. Then, the employed steel fibres are treated as spheroidal particles, and implanted into the MAA model for the design of a new UHPC. To demonstrate that the newly designed UHPC has superior performance, its macro and micro properties are analyzed in detail. The obtained experimental results reveal that the utilized steel fibre (L = 13 mm, d = 0.2 mm) can be treated as a spheroidal particle with a diameter of 5.65 mm in the MAA model. Moreover, based on the method proposed in this study, the negative effect of steel fibres on the packing system of UHPC can be minimized, which can enrich the basic design theory of UHPC composites. Highlights: A novel method for determining equivalent spherical diameter is proposed. . The equivalent spherical diameter of 13 mm steel fibres is calculated. Artificial neural network model for equivalent diameter prediction is built. The steel fibres is implanted into Modified Andreasen & Andersen model. An UHPC composite with advanced properties and dense matrix is developed.